5 - Concepts of Cabralism: On Cabral’s Intellectual Contributions - Nyoka, Bongani (Africa Development, 2017)
This article evaluates Reiland Rabaka’s book, Concepts of Cabralism: Amilcar Cabral and Africana Critical Theory. In the context of calls for knowledge ‘decolonisation’ on the African continent, the book is relevant and important for a variety of reasons. In the first instance, Rabaka traces the genealogy of Amilcar Cabral’s intellectual and political thought to leading figures of the Negritude Movement such as Aimé Césaire and Léopold Sédar Senghor, and then to Frantz Fanon. In doing so, Rabaka argues that, unlike other revolutionaries, Cabral avoided an uncritical regurgitation of orthodox Marxism. Instead, Cabral studied the concrete conditions of his locale not only to lead the liberation struggles of his people, but also to enrich revolutionary theory. In this regard, he was able to critique and, where necessary, dispense with some of the taken-for-granted categories of orthodox Marxism. Ultimately, Rabaka sees Cabral not only as a ‘revolutionary nationalist’ and ‘revolutionary humanist’, but also as a critical theorist. Consequently, he suggests that Cabral should be read as contributing to ‘Africana critical theory’. This article will take up each of these issues in its proper course.